2020
DOI: 10.1186/s12913-020-5009-x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing health service access by expanding disease coverage and adding patient navigation: challenges for patient satisfaction

Abstract: Background: Cancer control programs have added patient navigation to improve effectiveness in underserved populations, but research has yielded mixed results about their impact on patient satisfaction. This study focuses on three related research questions in a U.S. state cancer screening program before and after a redesign that added patient navigators and services for chronic illness: Did patient diversity increase; Did satisfaction levels improve; Did socioeconomic characteristics or perceived barriers expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Several strategies were used to support the process of data collection of patient experience. Twenty-five of the 36 studies included surveys that had been translated into multiple languages to aid completion [ 65 , 67 79 , 81 , 94 , 97 – 100 , 102 , 103 , 105 107 ]. Whilst using translated surveys was considered to enable a wider population to complete the surveys, no direct evidence of the impact of using translated surveys on the quality and quantity of data collected was reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies were used to support the process of data collection of patient experience. Twenty-five of the 36 studies included surveys that had been translated into multiple languages to aid completion [ 65 , 67 79 , 81 , 94 , 97 – 100 , 102 , 103 , 105 107 ]. Whilst using translated surveys was considered to enable a wider population to complete the surveys, no direct evidence of the impact of using translated surveys on the quality and quantity of data collected was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Just over half of the surveys used (20/36; 56%) were previously validated, English-language instrument(s) [ 64 , 65 , 67 , 71 , 72 , 74 77 , 79 , 94 , 98 , 101 , 103 – 106 , 108 , 109 ]. Of which, seven were adapted based on pilot testing with a subset of the target population [ 65 , 67 , 72 , 76 , 94 , 106 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research found an association between quality of care and patient satisfaction 57–60 . Accordingly, improving hospital quality in Germany, which aims primarily at better health outcomes, also helps to promote patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…54 Previous research found an association between quality of care and patient satisfaction. [57][58][59][60] Accordingly, improving hospital quality in Germany, which aims primarily at better health outcomes, also helps to promote patient satisfaction. Hospital websites were well known information sources about the hospital quality for the respondents (81.9%), but official quality reports published by hospitals were only known by 42.5%.…”
Section: Intermediate and Overall Goalsmentioning
confidence: 99%
“…Managed care and strategic purchasing options have been promoted as potential approaches to furthering the equity, access, and quality of recipient healthcare [2]. Both economics theory [3] and a large body of literature support the relationship between insurance coverage and access to care [4][5][6] as well as satisfaction with the care experience [7][8][9]. Five major areas are considered in evaluating the performance of HI policies: quality, accessibility, efficiency, continuity, and fairness [10].…”
Section: Introductionmentioning
confidence: 99%